Cuminaldehyde downregulates folate metabolism and membrane proteins to inhibit growth of Penicillium digitatum in citrus fruit - Okwong Oketch Reymick; Dazhao Liu; Xiaoli Tan; Qiuli OuYang; Nengguo Tao (Future Postharvest and Food)
Abstract In our previous study, cuminaldehyde triggered oxidative stress to inhibit growth of Penicillium digitatum in citrus fruit. Here, we examined the molecular mechanism by which it inhibited growth of P. digitatum. Results revealed a decline in content of glutathione and catalase activity from 10 and 20 min, respectively. Transcriptome and proteome data disclosed downregulation of proteins integral to mitochondrial electron transport chain (mETC) complexes I, IV, V, and transmembrane transporters. Catalase, regulators of transcription and replication, and biosynthesis of glutathione and folate were also downregulated. These were confirmed by RT‐qPCR analysis. Reduced expression of proteins integral to mETC complexes signaled possible damage to inner mitochondrial membrane. This was confirmed by decline in mitochondrial membrane potential with a concomitant decline in cellular ATP levels. mETC Complex I activity increased from 10 min which corresponded to the onset of rise in superoxide dismutase activity. The results suggest that cuminaldehyde instigated superoxide anion radicle production initially from mitochondrial complex I, while limiting the ability of the cells to scavenge the accumulating ROS by reducing the expression of glutathione and catalase. This was possibly achieved by downregulation of folate metabolism with the associated reduced expression of transcription regulators and proteins involved in glutathione biosynthesis.